2017
DOI: 10.1002/14651858.cd012010.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Serum amylase and lipase and urinary trypsinogen and amylase for diagnosis of acute pancreatitis

Abstract: As about a quarter of people with acute pancreatitis fail to be diagnosed as having acute pancreatitis with the evaluated tests, one should have a low threshold to admit the patient and treat them for acute pancreatitis if the symptoms are suggestive of acute pancreatitis, even if these tests are normal. About 1 in 10 patients without acute pancreatitis may be wrongly diagnosed as having acute pancreatitis with these tests, therefore it is important to consider other conditions that require urgent surgical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 238 publications
2
63
0
4
Order By: Relevance
“…Klinička prezentacija akutnog abdominalnog bola i nalazi dobiveni laboratorijskom dijagnostikom te slikovnim pretragama ukazivali su na nejasnu etiologiju bolova kod našeg pacijenta. Diferencijalno dijagnostički sumnjalo se na akutni pankreatitis, međutim, vrijednosti alfa amilaze u serumu su bile samo neznatno povišene, dok su kod pacijenata s akutnim pankreatitisom one tri puta veće od gornje granice referentnih vrijednosti 6 . CT nalaz je tek četvrtog dana hospitalizacije prikazao trombozu splanhničkih vena.…”
Section: Raspravaunclassified
“…Klinička prezentacija akutnog abdominalnog bola i nalazi dobiveni laboratorijskom dijagnostikom te slikovnim pretragama ukazivali su na nejasnu etiologiju bolova kod našeg pacijenta. Diferencijalno dijagnostički sumnjalo se na akutni pankreatitis, međutim, vrijednosti alfa amilaze u serumu su bile samo neznatno povišene, dok su kod pacijenata s akutnim pankreatitisom one tri puta veće od gornje granice referentnih vrijednosti 6 . CT nalaz je tek četvrtog dana hospitalizacije prikazao trombozu splanhničkih vena.…”
Section: Raspravaunclassified
“…In pancreatitis lipase and amylase tend to rise within the first few hours of symptom onset, with lipase remaining elevated for longer than amylase levels. 61 It is important to note that in up to 25% of cases serum amylase or lipase levels will not be elevated, necessitating need to consider imaging studies if the clinical presentation is suggestive of pancreatitis. 61 In our review, clozapine associated pancreatitis had a shorter duration of recovery (15.7 days) compared to hepatitis and nephritis cases.…”
Section: Clozapine Associated Pancreatitismentioning
confidence: 99%
“…61 It is important to note that in up to 25% of cases serum amylase or lipase levels will not be elevated, necessitating need to consider imaging studies if the clinical presentation is suggestive of pancreatitis. 61 In our review, clozapine associated pancreatitis had a shorter duration of recovery (15.7 days) compared to hepatitis and nephritis cases. A Swedish Nationwide database study identified an increased risk of pancreatitis with antipsychotic use, though this was not increased with clozapine or olanzapine use (OR 0.9 (0.6-1.4).…”
Section: Clozapine Associated Pancreatitismentioning
confidence: 99%
“…The diagnostic value of serum lipase and amylase in acute pancreatitis is unclear. Approximately 10% of patients may be incorrectly diagnosed with acute pancreatitis because of non-specific elevations in pancreatic enzymes [98]. A recent Cochrane review assessed the diagnostic accuracy of index pancreatic enzyme levels in patients who presented to the emergency department with abdominal pain.…”
Section: Cause and Risk Factorsmentioning
confidence: 99%
“…This could be partially related to delayed presentation for medical evaluation because of short half-life of serum amylase and lipase [99]. Among 100 patients with lipase and amylase levels less than three times the upper limit of normal, only 68 and 74 patients had acute pancreatitis, respectively [98]. There are many other causes of elevated lipase that could be misdiagnosed as acute pancreatitis [100].…”
Section: Cause and Risk Factorsmentioning
confidence: 99%